Client history and violence on direct care workers in the home care setting. Issue 12 (26th September 2016) - Byon, Ha Do; Storr, Carla; Edwards, Lori; Lipscomb, Jane
Abstract : Background: Health care workers providing home care are frequently unaware of their client's history of violence or mental illness/substance abuse disorder, recognized risk factors for workplace violence. This study estimated the associations between these factors and experiencing client violence among direct care workers in the home settings (DCWHs). Methods: Acts and threats of violence were estimated using data from an anonymous survey among DCWHs (n = 876) working at two large home care agencies. Logistic regressions were performed to produce odds ratios. Results: Physical acts and physical or verbal threats of client violence were associated with providing homecare to clients with a violence history (adjusted ORs = 6.60 and 10.78, respectively), whereas threats of client violence (adjusted OR = 5.80) were associated with caring for clients with a mental illness/substance abuse disorder. Conclusions: Policy and practices that support the communication of appropriate client risk information may reduce the likelihood of workplace violence among DCWHs. Am. J. Ind. Med. 59:1130–1135, 2016. © 2016 Wiley Periodicals, Inc.